Cutaneous malignancies: A prospective study of demographic patterns, risk factors, and clinical spectrum at a tertiary care center in South India - Shilpa Kanathur; Supriya Rajesh; Asha Gowrappala Shanmukhappa; Eswari Loganathan; Shwetha Suryanarayan (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: The incidence of skin cancer is increasing worldwide and is causing a massive burden to the health-care system. It arises as a result of interplay between various predisposing factors. We intend to study the various clinical presentations of cutaneous malignancies and the demographic pattern and risk factors associated with them. Methodology: The study was done over a period of 7 years, 181 patients were diagnosed with cutaneous malignancy in the department of dermatology of our tertiary care hospital. A diagnosis was done based on history, clinical and histopathological examination. Results: Of 181 patients, majority of the patients belonged to 7th decade (n = 56, 31%) with the mean age being 55 years. The study group had 105 males (58%) and 76 (42%) females. The most common site was the head-and-neck region (n = 105, 58%). The most important associated condition/predisposing factor was ultraviolet (UV) radiation exposure (n = 79, 44%). Keratinocytic tumors formed the largest group (n = 131, 72%) in which basal cell carcinoma (BCC) was the most common (n = 75, 41%). Surgical excision was the main modality of treatment and was done in 111 (61%) patients. Conclusion: BCC was the most common skin cancer with head-and-neck region being the most common location in our study. Important risk factors were increasing age, male sex, and prolonged exposure to UV radiation. Early diagnosis helps in planning effective management strategies.